Measuring security price performance - Brown, Stephen J.; Warner, Jerold B. (Journal of Financial Economics, 1980)
Event studies focus on the impact of particular types of firm-specific events on the prices of the affected firms' securities. In this paper, observed stock return data are employed to examine various methodologies which are used in event studies to measure security price performance. Abnormal performance is introduced into this data. We find that a simple methodology based on the market model performs well under a wide variety of conditions. In some situations, even simpler methods which do not explicitly adjust for marketwide factors or for risk perform no worse than the market model. We also show how misuse of any of the methodologies can result in false inferences about the presence of abnormal performance.